2012
DOI: 10.1100/2012/351074
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Accumulation and the Genotoxicity in Barbel (Barbus barbus) as Indicators of the Danube River Pollution

Abstract: The aim of this study was to analyze 16 trace elements (Al, As, B, Ba, Cd, Co, Cr, Cu, Fe, Li, Mn, Mo, Ni, Pb, Sr, and Zn) in different barbel (Barbus barbus) tissues and to detect the presence of genotoxic effects in erythrocytes with the alkaline comet assay. Barbel specimens were collected in the Danube river near Belgrade, Serbia, where the discharge of untreated communal and industrial wastewaters is likely to produce negative effects on fish residing in this area. The highest concentrations of Sr, Mn, Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…Fish liver accumulates the highest Cu levels (Rashed, 2001), since Cu represents an inherent part of the enzymes localized in the liver (Kenšova et al, 2010). The highest Al and Sr concentrations were found in gills, which is in line with previous studies on the Danube fish (Višnjić-Jeftić et al, 2010;Jarić et al, 2011;Sunjog et al, 2012). In the present study, there was no clear relationship observed between the fish length and the elemental accumulation.…”
Section: Discussionsupporting
confidence: 79%
“…Fish liver accumulates the highest Cu levels (Rashed, 2001), since Cu represents an inherent part of the enzymes localized in the liver (Kenšova et al, 2010). The highest Al and Sr concentrations were found in gills, which is in line with previous studies on the Danube fish (Višnjić-Jeftić et al, 2010;Jarić et al, 2011;Sunjog et al, 2012). In the present study, there was no clear relationship observed between the fish length and the elemental accumulation.…”
Section: Discussionsupporting
confidence: 79%
“…The highest Al concentrations were found in gills, which are in line with previous studies of Višnjić-Jeftić et al [6], Jarić et al [7], Lenhardt et al [25], and Sunjog et al [47], but not in line with Saygi et al [48], who found the highest concentrations of Al in liver. Muscle samples from catfish (1.93 mg·kg -1 ww) had higher concentrations of Al than Danube samples (ND -not detected) [25], but lower than other samples from the Danube (7.50 μg·g -1 dw) [27].…”
Section: Resultssupporting
confidence: 81%
“…We have also detected genotoxic pollution in the Danube River in studies performed on Barbus barbus [47] and Sinanodonta woodiana [48], as well as in the tributary Velika Morava by S. woodiana [21]. Moreover, the deterioration of water quality of the Danube River and the Danube tributaries by anthropogenic impact was shown in our previous studies [48][49][50][51][52].…”
Section: Genotoxicity Monitoring Of the Lower Flow Of The Sava Rivermentioning
confidence: 59%